2018
DOI: 10.1155/2018/2541020
|View full text |Cite
|
Sign up to set email alerts
|

The Activity Concentrations and Radium Equivalent Activity in Soil Samples Collected from the Eastern Part of Basrah Governorate in Southern Iraq

Abstract: Clay soil samples (0, 30, and 60 cm depths) were collected from two districts (Abu Al Khasib and Ad Dayr) in Basrah governorate in southern Iraq for gamma-ray spectroscopy. The activity concentrations for natural existing radionuclides in 18 soil samples were measured using high-purity germanium detector HPGe. From the obtained results of γ-ray spectroscopy, the 238U activity concentrations were found to be ranging from 2.4 to 5.6 ppm with an average of 3.5 ppm in Abu Al Khasib and ranging from 2.1 to 4.5 ppm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The calculated radiation exposure values of R activity , I r , and D aedr are shown in Table 4 . The results showed that both the R activity and I r of most sampling sites significantly exceeded the recommended limit values ( R activity limit value was 370 Bq·kg −1 while I r was 1 [ 25 , 26 , 27 ]). Specifically, both the R activity and I r of S1, S2, S4, S5, and S7 were approximately 1.9, 22, 50, 75, and 3.3 times the limit value, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The calculated radiation exposure values of R activity , I r , and D aedr are shown in Table 4 . The results showed that both the R activity and I r of most sampling sites significantly exceeded the recommended limit values ( R activity limit value was 370 Bq·kg −1 while I r was 1 [ 25 , 26 , 27 ]). Specifically, both the R activity and I r of S1, S2, S4, S5, and S7 were approximately 1.9, 22, 50, 75, and 3.3 times the limit value, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…where m is the mass of the isotope in the given sample of mass M with activity of B ( B in Bq/kg and m and M in kg), A = mass number, N 0 = Avogadro number and  is the Decay constant (= 0.693/ T 1/2 ) (Rasha et al, 2018).…”
Section: (1)mentioning
confidence: 99%
“…On the other hand, a pH value of less than 6 occurs so often in nature that is considered as neutral. However, since the soil can alter the water pH and majority of crops have pH tolerance at a wide range of water pH [3], thus the pH of irrigation water is not a reliable parameter for water quality.…”
Section: Characteristic Of Surface Water and Groundwatermentioning
confidence: 99%
“…The excessive amounts of colloidally adsorbed Na break down the soil physical structure, leading to rigid and dense soil when it is dry and gradually becomes impenetrable to water infiltration. It is important to note that when sandy soils are irrigated with high SAR water, it is not easily depraved as compared to other type of soils [3].…”
Section: Salinity and Sodicity Hazards Of Surface And Ground Watersmentioning
confidence: 99%